2021
DOI: 10.1016/j.jare.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen prevent atherosclerosis by attenuating endothelial cell pyroptosis via activation of estrogen receptor α-mediated autophagy

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 57 publications
3
80
0
1
Order By: Relevance
“…The reaction can ameliorate atherosclerosis as early as possible, usually before the menopausal stage. 224 Trimethylamine N‐oxide (TMAO) is usually generated from the phosphatidylcholine metabolism of gut flora, which also presents as a danger signal for cardiovascular diseases. TMAO promotes ROS‐induced pyroptosis in vascular ECs through the upregulation of the succinate dehydrogenase complex subunit B (SDHB), thereby contributing to the progression of atherosclerotic lesions.…”
Section: The Relationship Between Pyroptosis and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction can ameliorate atherosclerosis as early as possible, usually before the menopausal stage. 224 Trimethylamine N‐oxide (TMAO) is usually generated from the phosphatidylcholine metabolism of gut flora, which also presents as a danger signal for cardiovascular diseases. TMAO promotes ROS‐induced pyroptosis in vascular ECs through the upregulation of the succinate dehydrogenase complex subunit B (SDHB), thereby contributing to the progression of atherosclerotic lesions.…”
Section: The Relationship Between Pyroptosis and Metabolismmentioning
confidence: 99%
“…As for estrogen, it inhibits pyroptosis in vascular ECs mainly through the estrogen receptor alpha (ER‐α)‐mediated activation of autophagy. The reaction can ameliorate atherosclerosis as early as possible, usually before the menopausal stage 224 . Trimethylamine N‐oxide (TMAO) is usually generated from the phosphatidylcholine metabolism of gut flora, which also presents as a danger signal for cardiovascular diseases.…”
Section: The Relationship Between Pyroptosis and Metabolismmentioning
confidence: 99%
“…On the other hand, existing studies have indicated that multiple drugs and genes such as melatonin, salidroside (SAL), estrogen, pyrogallol-phloroglucinol-6,6-bieckol (PPB) and fibroblast growth factor 21 (FGF21) decrease atherosclerosis plaque formation via inhibiting ECs pyroptosis in vivo and in vitro ( Zhang et al, 2018 ; Oh et al, 2020 ; Xing et al, 2020 ; Zeng et al, 2020 ; Meng et al, 2021 ). Moreover, recent studis have discovered more drugs and miRNAs that could regulate ECs pyroptosis, including atorvastatin, miRNA-30c-5p, miRNA-125a-5p, etc.…”
Section: Pyroptosis In Atherosclerosismentioning
confidence: 99%
“…A recent study showed that estrogen inhibits ECs pyroptosis by inducing autophagy, thereby ameliorating atherosclerosis in mice. Estrogen reduced the expression of caspase-1 and GSDMD in homocysteine (Hcy)-treated HUVECs, while the autophagy inhibitor 3-MA reversed this effect ( Meng et al, 2021 ). Meanwhile, Jiang et al reported that autophagy alleviates the activation of NLRP3 inflammasome and pyroptosis caused by acrolein in ECs via improving mitochondrial function and reducing ROS ( Jiang et al, 2018 ).…”
Section: Pyroptosis In Atherosclerosismentioning
confidence: 99%
“…Torii et al found that the lysosomal inhibitor Baf-A1 reduces ferroptosis of tumor cells ( 20 ). It has been previously suggested that the autophagy-lysosome pathway inhibits CVD progression ( 21 , 22 ). However, most of the current studies on the relationship between the autophagy-lysosome pathway and ferroptosis have focused on tumor cells with the findings suggesting that autophagy promotes ferroptosis.…”
Section: Role Of Organelles In the Regulation Of Ferroptosismentioning
confidence: 99%